Reality of pedagogical practice in times of pandemic - Sanchez Bozo, Carelis Beatriz (2021)
The objective was to analyze the reality of the pedagogical practice and to know what has been the turn that the pandemic has caused in the institutions of secondary education; To achieve this, the quantitative methodology was used with the application of descriptive statistics. Evidence that 66.67% do not agree to integrate the methodological strategies of technological pedagogy into their pedagogy while 77.78% claim not to assume the new pedagogical methods within the formative dynamics. It was concluded that the pedagogy developed is attached to the face-to-face paradigm only with the change in resources and means. The complexity of the situation is more related to the willingness and interest of the institutions that must internalize the achievement of educational quality through innovation.